A Quantum-Mechanical Looking Behind the Scene of the Classic G·C Nucleobase Pairs Tautomerization - Brovarets', Ol'ha O.; Muradova, Alona; Hovorun, Dmytro M. (Frontiers in Chemistry, 2020)
For the first time it was provided comprehensive quantum-mechanical (QM) investigation of the physico-chemical mechanisms of the tautomeric wobblization of the four biologically-important G∙C DNA base pairs by the participation of the monomers in the rare, in particular mutagenic tautomeric forms (marked with an asterisk), at the MP2/aug-cc-pVDZ//B3LYP/6-311++G(d,p) level of QM theory. This novel tautomeric transformation (wobblization) is intrinsically inherent property of the G∙C DNA base pairs. In this study, a number of interesting results has been obtained, which lie far beyond the existing representations. It was shown that Löwdin’s G*∙C*(WC) DNA base pair does not tautomerize by its wobblization. Tautomeric wobblization of the G*∙C*(rWC) (“r” - reverse, “WC” – Watson-Crick) and G*t∙C*(H) (“H” – Hoogsteen) base pairs (“t” – denotes base in trans position) is preceded by the stages of the tautomerization by the single proton transfer. It was established that the G*t∙C*(rH) base pair can be wobbled through the two pathways by the traditional one-stage mechanism through the TSs, which are tight G+∙C- ion pairs, stabilized by the participation of only two intermolecular H-bonds. It was found out that most probably the G∙C base pair is incorporated into the DNA double helix with parallel strands in the form of the G*∙C*(rWC), G∙C*(rwwc) and G*∙C(rwwc) (“w” – wobble) tautomers, which are in rapid tautomeric equilibrium with each other. It was proved that the G*∙C*(rWC) nucleobase pair is also in the rapid tautomeric equilibrium with the 8 tautomeric forms of the Levitt base pair. It was revealed view cases of the tautomerization of the base pairs by the participation of the C8H group of the guanine. It was shortly discussed possible biological role of the obtained results.